2019
DOI: 10.1177/0894845319832672
|View full text |Cite
|
Sign up to set email alerts
|

Chinese International Students’ Expectations About Career Counseling

Abstract: Chinese international students are the largest international student body (33.19%) in the United States. However, career services on college campuses are underutilized by this population despite their pressing needs for career guidance. Chinese international students’ expectations about career counseling may explain the disconnection between needs and service utilization. Although clients’ expectations about counseling have been studied extensively, no study has focused on Chinese international students’ expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…'s (2003) study, as well as people's reliance on various types of technology (e .g ., the internet, smartphone, apps) for information and advice in today's society, participants in our study may have believed that the CACG system could and should provide answers or direction for each survey item . Indeed, our results suggest that the students in this study tended to want CACG systems to be highly directive, which is consistent with findings by Paszkowska-Rogacz (2008) and Li et al . (2021) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…'s (2003) study, as well as people's reliance on various types of technology (e .g ., the internet, smartphone, apps) for information and advice in today's society, participants in our study may have believed that the CACG system could and should provide answers or direction for each survey item . Indeed, our results suggest that the students in this study tended to want CACG systems to be highly directive, which is consistent with findings by Paszkowska-Rogacz (2008) and Li et al . (2021) .…”
Section: Discussionsupporting
confidence: 92%
“…Zysberg (2010) found that effective management of expectations for career counseling predicted greater satisfaction at the conclusion of services in a sample of Israeli undergraduates . Finally, qualitative research by Li et al . (2021) indicated that Chinese students expected both guidance and access to relevant information during career counseling .…”
Section: Client Expectationsmentioning
confidence: 99%
“…Further exacerbating the situation is the intersectionality of gender and race (Li et al, 2019; Ratts, 2017), which is known to influence cultural identity during adolescence (Chan et al, 2018). Although counseling literature is replete with studies indicating male privilege, being male does have unique drawbacks and limitations when the individual is a person of color (McDonald et al, 2019).…”
Section: Asian American Masculinitymentioning
confidence: 99%
“…Issues regarding cultural and gender identity development are not necessarily new (especially for males of color), but the problem arises in the lack of interventions and research for young Asian Americans that target these issues within a school setting (Butler & Shillingford-Butler, 2014; C. Y. Chang & O’Hara, 2013; Li et al, 2019; Sue & Sue, 2016). Stemming from an unconscious belief in the model minority myth, school counselors sometimes overlook these concerns encountered by Asian American male students.…”
Section: Asian American Masculinitymentioning
confidence: 99%
See 1 more Smart Citation